2023
DOI: 10.3390/ijms24087082
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism Is Altered in Radioresistant Rectal Cancer

Abstract: Resistance to neoadjuvant chemoradiation therapy is a significant clinical challenge in the management of rectal cancer. There is an unmet need to identify the underlying mechanisms of treatment resistance to enable the development of biomarkers predictive of response and novel treatment strategies to improve therapeutic response. In this study, an in vitro model of inherently radioresistant rectal cancer was identified and characterized to identify mechanisms underlying radioresistance in rectal cancer. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…We and others have previously characterised these in vitro models of CRC, demonstrating SW837 rectal cells as a robust model of radioresistant rectal cancer (23,48,49). We have previously demonstrated that SW837 cells have a reduced reliance on glycolysis, supporting a role for enhanced mitochondrial metabolism in the radioresistance of these cells (23). In this study, metformin was demonstrated to significantly inhibit oxidative phosphorylation and enhance glycolytic rates in both HCT116 and SW837 cells, supporting it as an ETC inhibitor in CRC.…”
supporting
confidence: 61%
See 4 more Smart Citations
“…We and others have previously characterised these in vitro models of CRC, demonstrating SW837 rectal cells as a robust model of radioresistant rectal cancer (23,48,49). We have previously demonstrated that SW837 cells have a reduced reliance on glycolysis, supporting a role for enhanced mitochondrial metabolism in the radioresistance of these cells (23). In this study, metformin was demonstrated to significantly inhibit oxidative phosphorylation and enhance glycolytic rates in both HCT116 and SW837 cells, supporting it as an ETC inhibitor in CRC.…”
supporting
confidence: 61%
“…In this study, SW837 rectal cancer cells, and HCT116 colon cancer cells were utilised as an in vitro model of inherently radioresistant, and radiosensitive CRC, respectively. We and others have previously characterised these in vitro models of CRC, demonstrating SW837 rectal cells as a robust model of radioresistant rectal cancer (23,48,49). We have previously demonstrated that SW837 cells have a reduced reliance on glycolysis, supporting a role for enhanced mitochondrial metabolism in the radioresistance of these cells (23).…”
mentioning
confidence: 78%
See 3 more Smart Citations